Efektivitas Penerapan Model Pembelajaran Problem Based Learning (PBL) Berbasis Etnomatematika untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis - Retno Widyaningrum; Syaula Fitriyah Rani (Indonesian Mathematics Education Journal, 2025)
Problem solving ability is an important competency that elementary school students must have because it is useful in everyday life. However, this ability is still an obstacle in learning mathematics. Many students have difficulty in solving problems on the surface area of ​​a cube that is packaged in story problems. In an effort to overcome this, researchers conducted research on mathematics learning using the PBL learning model based on ethnomathematics. This study aims to describe the implementation of the PBL learning model based on ethnomathematics, describe students' problem solving abilities after the PBL learning model based on ethnomathematics is applied, and to describe the effectiveness of the PBL learning model based on ethnomathematics to improve problem solving abilities. This study uses a quantitative approach with a quasi-experimental type. The sampling technique uses simple random sampling, and data is collected through observation and testing. The results of the study showed (1) the implementation of the PBL model based on ethnomathematics reached 84% at the first meeting and 94% at the second meeting. (2) students' mathematical problem solving abilities increased after being given the PBL learning model with an average score of 86.11. (3) The Ancova test showed a significant difference between the control and experimental classes. In the N-Gain test, the control class obtained a result of 17% and the experimental class 64%. So it can be concluded that the Problem Based Learning model based on ethnomathematics is quite effective in improving students' mathematical problem solving abilities